Single crystal growth and physical property characterization of ternary phosphide chalcogenide ZrP1.49Se0.51. (June 2020) - Li, Meng; Meng, Yan; Yi, Xiaolei; Xing, Xiangzhuo; Xu, Chunqiang; Feng, Jiajia; Lin, Bencheng; Li, Wenchong; Tamegai, Tsuyoshi; Shi, Zhixiang
Abstract: High-quality and sizable single crystals are essential for studying the intrinsic properties of a novel superconductor. Here for the first time we report the successful growth of millimeter-size single crystals of ZrP1.49 Se0.51 with PbFCl-type structure by using a chemical vapor transport technique. Owing to the availability of the high-quality single crystals, intrinsic properties in both superconducting and normal states are systematically characterized by means of electrical transport, magnetization, and specific heat measurements. ZrP1.49 Se0.51 single crystals show bulk superconductivity with a critical transition temperature T c of 6.8 K. It is found that the temperature dependence of upper critical field μ 0 H c2 ( T ) deviates from the conventional Werthamer-Helfand-Hohenber (WHH) model. μ 0 H c2 ( T ) shows a moderate anisotropy ( Γ = H c2, ab ( T )/ H c2, c ( T )), which resides in the range 4.47–4.63 and shows a nonmonotonic temperature dependence, similar to the multiband iron-based superconductors. Moreover, the results of lower critical field and thermodynamic properties reveal that ZrP1.49 Se0.51 is a weakly electron–phonon coupled type-II BCS superconductor. Highlights: Millimeter-size ZrP1.49 Se0.51 single crystals were synthesized by using a CVT technique for the first time. Intrinsic properties are systematically characterized by means of electrical transport, magnetization, and specific heat measurements.